Catalog of type specimens of IEB herbarium (Mexico) - Ocampo Acosta, Gilberto; Medellín Villamil, Ana Lilia (Instituto de Ecología, A.C., 2004)
In this paper a catalog of type specimens of vascular plants held in the herbarium of the Instituto de Ecología, A.C., located in Pátzcuaro, Michoacán, Mexico (IEB), is provided. The collection includes 340 specimens designed as primary types (85 holotypes, 247 isotypes, 2 neotypes and 6 isoneotypes), which represent the nomenclatural reference for 286 taxa.